Field assessment of surface water-groundwater connectivity in a semi-arid river basin (Murray-Darling, Australia) - Lamontagne, S.; Taylor, A. R.; Cook, Peter G.; Crosbie, R. S.; Brownbill, R.; Williams, R. M.; Brunner, Philip (My University, 2014)
In semi-arid and arid river basins, understanding the connectivity between rivers and alluvial aquifers is one of the key challenges for the management of groundwater resources. The type of connection present (gaining, losing-connected, transitional and losing-disconnected) was assessed at 12 sites along six Murray-Darling Basin river reaches. The assessments were made by measuring the hydraulic head in the riparian zone near the rivers to evaluate if the water tables intersected the riverbeds and by measuring fluid pressure () in the riverbeds. The rationale for the latter was that will always be greater than or equal to zero under connected conditions (either losing or gaining) and always lesser than or equal to zero under losing-disconnected conditions. A mixture of losing-disconnected, losing-connected and gaining conditions was found among the 12 sites. The losing-disconnected sites all had a riverbed with a lower hydraulic conductivity than the underlying aquifer, usually in the form of a silty clay or clay unit 0.5-2m in thickness. The riparian water tables were 6 to 25m below riverbed level at the losing-disconnected sites but never lower than 1m below riverbed level at the losing-connected ones. The contrast in water table depth between connected and disconnected sites was attributed to the conditions at the time of the study, when a severe regional drought had generated a widespread decline in regional water tables. This decline was apparently compensated near losing-connected rivers by increased infiltration rates, while the decline could not be compensated at the losing-disconnected rivers because the infiltration rates were already maximal there. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: murray-darling basin; groundwater-surface water interactions; losing streams; stream; aquifer; depletion; salinity; sediment; modflow; seepage; models; zone; flow